PRACTISING IMAM AL-GHAZALI'S MORAL CONCEPTS IN MADRASAH ALIYAH NEGERI 2 MODEL PADANG SIDEMPUAN - M. Azhari (Program Pascasarjana UIN Sumatera Utara, 2022)
Abstract: Islamic education is a conscious effort that is planned to prepare students to believe, understand, appreciate and practice Islamic teachings. The purpose of this study is to describe the concept of morality in Islamic education. This study used a qualitative approach, the background at Madrasah Aliyah Negeri 2 Model Padang Sidempuan, the data sources in this study included primary data sources and secondary data sources, data collection techniques were carried out by observation, interviews and documentation. Observations are made to observe learning activities. Interviews were conducted with teachers and students. Documentation is used to find out the history of the school, vision and mission, teacher condition, number of students, school infrastructure, school geographical location and school organizational structure. In the technique of guaranteeing the validity of the data is used triangulation. While the data analysis technique uses descriptive qualitative analysis. The results of this study indicate that the concept of morality in Islamic education from the perspective of Imam Al-Ghazali at Madrasah Aliyah Negeri 2 Model Padang Sidempuan with four aspects, namely: 1) Faith Education 2) Moral Education 3) Aqliah Education 4) Social Education and the method of forming it by example, stories, punishments and rewards have been running and it can be concluded that with the implementation of the concept of Islamic education in the perspective of Imam Al-Ghazali, students become Muslim individuals who are pious, prevent themselves from lust, and have noble character, discipline, sportsmanship, responsibility, spirit of cooperation, and obedience to Allah and His Messenger, respect for parents and love for others.